Peran Pemerintah Desa terhadap Desa Adiwiyata di Desa Ulumahuam - Nia Andriani; Faridatul Hikmah; Alyaumi Hasanah Siregar; Febri Shaleh Siregar; Yani Lubis (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
The village is a combination relationship between the activities of a group of people and their environment caused by social and cultural elements. Village government is a government institution that runs and manages village areas. In addition to its environment, Ulamahuam village also has tourist attractions that increase the economic income of residents. This tourist attraction is managed and utilized from natural resources in Ulumahuam Village, Pandayangan hamlet. These natural resources require human resources in the village, to manage tourism objects in order to increase the attraction of visitors. To create a village that cares and has an environmental culture, residents need to be involved in various environmental learning activities. In addition, the village head is also expected to involve the surrounding community in carrying out various activities that provide benefits for both the community and the environment. The role of the village government in the village of Ulamahuam is to carry out socialization to the village community about the Adiwiyata village program, after that the community applies reforestation along the road and then the community manages the natural resources owned in the village so as to generate income for the village, in the village of Ulamahuam still maintaining customs. Keywords: Adiwiyata village, environment